Synthesis and applications of plasmonic metal nanostructures - Tan, Jillian Jing Wen. (2013)
More than 12.6 million people in the world are diagnosed with cancer every year, with at least 7.5 million dying of this disease (1). A research by the World Health Organization stated that this figure continues to rise in every country as the population grows and people live longer. Fluorescence is one of the most important tools for cancer cells detection. However, its sensitivity is limited by certain problems such as photobleaching, narrow excitation with broad emission profiles, and peak overlapping in multiplexed experiments (2). Two studies related to metal enhanced fluorescence (MEF) were analyzed. The fluorescent dye molecules showed strong plasmonic interactions with a metal core which increases the fluorescence signal. This phenomenon is observed between a metal core and metal nanoparticles as well.